Enhanced removal of nickel(II) ions from aqueous solutions by SDS-functionalized graphene oxide - ÇALIŞKAN SALİHİ, ELİF (TAYLOR & FRANCIS INC, 2016)
In this paper, a one-pot and easy-to-handle method at room temperature without additional chemicals for the modification of graphene oxide (GO) with surfactant is found. Removal of nickel (II) ions from aqueous solutions by GO and surfactant (sodium dodecyl sulphate) modified graphene oxide (SDS-GO) was studied spectrophotometrically at room temperature as a function of time, initial concentration and pH. Adsorption capacity of the adsorbent was increased dramatically (from 20.19 to 55.16 mg/g found by Langmuir model) due to the functionalization of the surface by SDS. The driving force of the adsorption of Ni(II) ions is electrostatic attraction and Ni(II) ions adsorbed on the GO surface chemically besides ion exchange.
Keywords: Adsorption; graphene; nanomaterials; CATALYZE REVERSIBLE HYDRATION; MINERALIZATION CARBON CAPTURE; HEAVY-METAL IONS; WASTE-WATER; ACTIVATED CARBONS; ADSORPTION; NANOTUBES; EQUILIBRIUM; SURFACES; NANOPARTICLES